The Problem Of Numeration Difficulties (Dyscalculia) In Children: Systematic Literature Review - Fatkhul Arifin; Asep Supena (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This research aims to find the main themes and research categories regardingnumeracy difficulties (Dyscalculia). For the data taken to fulfil the objectives of this research, the author searched for several relevant sources from Google Scholar and Scopus (SAGE et al.& Francis). Four combinations of keywords determined articles; then the articles were included in the data collection, and researchers applied a systematic literature review method. Articles that will be research sources are limited to the last six years. The dominant researchmethodology of the articles reviewed is qualitative. The four main themes revealed from the qualitative content analysis are dyscalculia, causes of dyscalculia, cases of dyscalculia, and solutions to overcome dyscalculia. Articles are filtered starting from topic description, eligibility criteria and search strategy. The total number of articles reviewed was 198 from different sources, namely Springer, Elsevier, SAGE, Eric, and Taylor & Francis. Then, it was reviewed again to obtain 87 articles. Then, reviewed again according to the theme in the title, 50 articles were found that were most suitable. Of the 50 articles that are most suitable for deeper study, dyscalculia occurs throughout the world. The cause of dyslexia can be due to developmental errors during pregnancy or other factors such as physical defects or the child'shabits. The solution offered by the teacher is to use several learning methods and media that are appropriate for the child's condition.